2009
DOI: 10.1063/1.3207885
|View full text |Cite
|
Sign up to set email alerts
|

Drag reduction in turbulent flows over superhydrophobic surfaces

Abstract: In this paper, we demonstrate that periodic, micropatterned superhydrophobic surfaces, previously noted for their ability to provide laminar flow drag reduction, are capable of reducing drag in the turbulent flow regime. Superhydrophobic surfaces contain micro or nanoscale hydrophobic features which can support a shear-free air-water interface between peaks in the surface topology. Particle image velocimetry and pressure drop measurements were used to observe significant slip velocities, shear stress, and pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
399
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(418 citation statements)
references
References 28 publications
18
399
0
1
Order By: Relevance
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The recent numerical (Martell et al 2009(Martell et al , 2010Park et al 2013) and experimental (Daniello et al 2009) results under turbulent flow conditions have shown that SHPo surfaces with even a moderate slip length (~10 µm) can result in significant turbulent drag reduction, as the turbulent structures become weakened near the SHPo surface and a thin viscous sublayer becomes the main characteristic fluidic length scale in the turbulent flow. Recently, using regular-structured SHPo surfaces of large slip lengths, drag reductions as much as 75 % have been reported in turbulent boundary layer flows (Park et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…3 A-C, SI Experimental Protocols, and Tables S3 and S4). Similar to earlier work (10,13,24), our SHSs were made of hydrophobic polydimethylsiloxane (PDMS), using photolithography techniques. The SHSs consisted of stream-wise parallel rectangular lanes or gratings, as shown in Fig.…”
Section: Experiments Show Reduced Slipmentioning
confidence: 99%
“…6-11) and rheometer tests reported slip lengths of up to 185 µm (12). Turbulent flow experiments have reduced drag by up to 75% (13)(14)(15)(16). However, a wide range of experiments have provided inconsistent results, with several studies reporting little or no drag reduction (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…In particular, the formation of hierarchical structures is integral to forming superhydrophobic surfaces [10]. The ridge type of structures on shark skin aid their drag reduction [11] and similar ridge type structures have suggested by Rothstein et al [12,13] as possible drag reducing artificial surfaces. Therefore, a subsidiary aim in this article is to introduce approach to forming ridge-type drag reducing SU8 structures.…”
Section: Introductionmentioning
confidence: 99%